Sistem Pendukung Keputusan Pemilihan Lokasi Dealer Motor Honda di Bali Berbasis Ontologi - Fadillah, Andien Rachma; Mogi, I Komang Ari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Motorcycle is one of the needs that can be said as a necessity that must be owned by everyone, especially in the field of transportation. The use of motorbikes which are more in demand by the public is certainly not without reason given the increasingly dense means of transportation in Indonesia today. The use of a motorcycle can minimize the use of time because it is considered more effective on the trip. By choosing the right location for selling motorcycles or better known as Dealers, especially Honda Dealers in Bali, it will certainly determine the level of success, or the number of sales generated. Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method is expected to help determine priorities from various available alternative locations. The application of the Analytical Hierarchy Process (AHP) method in this study is to determine the location for the construction of a Honda Motorcycle Dealer in Bali according to the desired criteria. The Analytical Hierarchy Process (AHP) method will make it easier to make decisions. Based on the calculation of the Analytical Hierarchy Process (AHP), the priority criteria are obtained in determining the selection of development sites where the criteria are Market Share, targets and competitors. The highest ranking in the selection of Motorcycle Dealer locations in Bali, especially in Tabanan Regency, was obtained by Baturiti District with the results of the eigenvalues of 0.455.